Keeping the campfires going : Native women's activism in urban communities - Krouse, Susan Applegate, 1955-2010; Howard-Bobiwash, Heather, 1966- (Book collections on Project MUSE., 2009)
The essays in this groundbreaking anthology, Keeping the Campfires Going, highlight the accomplishments of and challenges confronting Native women activists in American and Canadian cities. Since World War II, Indigenous women from many communities have stepped forward through organizations, in their families, or by themselves to take action on behalf of the growing number of Native people living in urban areas. This collection recounts and assesses the struggles, successes, and legacies of several of these women in cities across North America, from San Francisco to Toronto, Vancouver to Chica.